2018
DOI: 10.1093/eurheartj/ehy136
|View full text |Cite
|
Sign up to set email alerts
|

The 2018 European Heart Rhythm Association Practical Guide on the use of non-vitamin K antagonist oral anticoagulants in patients with atrial fibrillation

Abstract: The current manuscript is the second update of the original Practical Guide, published in 2013 [Heidbuchel et al. European Heart Rhythm Association Practical Guide on the use of new oral anticoagulants in patients with non-valvular atrial fibrillation. Europace 2013;15:625-651; Heidbuchel et al. Updated European Heart Rhythm Association Practical Guide on the use of non-vitamin K antagonist anticoagulants in patients with non-valvular atrial fibrillation. Europace 2015;17:1467-1507]. Non-vitamin K antagonist o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

23
1,810
1
258

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 1,743 publications
(2,183 citation statements)
references
References 444 publications
23
1,810
1
258
Order By: Relevance
“…*Adapted from manufacturers’ SPCs and with reference to Steffel et al 95; consulting BNF and local guidelines also suggested.†Strong inhibitors of both CYP3A4 and P-gp: ketoconazole, itraconazole, voriconazole, posaconazole, dronedarone, HIV protease inhibitors (increased anticoagulant effect).‡Other inhibitors of CYP3A4 and P-gp (ie, with less potent inhibition of one or both pathways): clarithromycin, erythromycin, fluconazole (increased anticoagulant effect).§CYP3A4 inducers: rifampicin, phenytoin, carbamazepine, phenobarbitone, St. John’s wort (reduced anticoagulant effect).¶Strong P-gp inhibitors: as †, also ciclosporin, tacrolimus and erythromycin (increased anticoagulant effect).**Other P-gp inhibitors: verapamil (note dose reduction for dabigatran), amiodarone, quinidine, clarithromycin, ticagrelor (increased anticoagulant effect).††P-gp inducers: rifampicin, phenytoin, carbamazepine, phenobarbitone, St. John’s wort (reduced anticoagulant effect).Major warfarin interactions: allopurinol, azoles, omeprazole, amiodarone, tamoxifen, statins (especially fluvastatin), fibrates, erythromycin, metronidazole (increased effect); phenobarbitone, primidone, carbamazepine, rifampicin, phenytoin, azathioprine, St. John’s wort (reduced effect); steroids, nevirapine, ritonavir (unpredictable effects); liver, broccoli, sprouts, leafy greens (high vitamin K content—reduced effect).AF, atrial fibrillation; INR, international normalised ratio; N/A, not applicable.…”
Section: Starting An Anticoagulantmentioning
confidence: 99%
See 3 more Smart Citations
“…*Adapted from manufacturers’ SPCs and with reference to Steffel et al 95; consulting BNF and local guidelines also suggested.†Strong inhibitors of both CYP3A4 and P-gp: ketoconazole, itraconazole, voriconazole, posaconazole, dronedarone, HIV protease inhibitors (increased anticoagulant effect).‡Other inhibitors of CYP3A4 and P-gp (ie, with less potent inhibition of one or both pathways): clarithromycin, erythromycin, fluconazole (increased anticoagulant effect).§CYP3A4 inducers: rifampicin, phenytoin, carbamazepine, phenobarbitone, St. John’s wort (reduced anticoagulant effect).¶Strong P-gp inhibitors: as †, also ciclosporin, tacrolimus and erythromycin (increased anticoagulant effect).**Other P-gp inhibitors: verapamil (note dose reduction for dabigatran), amiodarone, quinidine, clarithromycin, ticagrelor (increased anticoagulant effect).††P-gp inducers: rifampicin, phenytoin, carbamazepine, phenobarbitone, St. John’s wort (reduced anticoagulant effect).Major warfarin interactions: allopurinol, azoles, omeprazole, amiodarone, tamoxifen, statins (especially fluvastatin), fibrates, erythromycin, metronidazole (increased effect); phenobarbitone, primidone, carbamazepine, rifampicin, phenytoin, azathioprine, St. John’s wort (reduced effect); steroids, nevirapine, ritonavir (unpredictable effects); liver, broccoli, sprouts, leafy greens (high vitamin K content—reduced effect).AF, atrial fibrillation; INR, international normalised ratio; N/A, not applicable.…”
Section: Starting An Anticoagulantmentioning
confidence: 99%
“…*Adapted from manufacturers’ SPCs and with reference to Steffel et al 95; consulting BNF and local guidelines also suggested.…”
Section: Starting An Anticoagulantmentioning
confidence: 99%
See 2 more Smart Citations
“…On the basis of pharmacological modelling, rivaroxaban, apixaban and edoxaban (but not dabigatran) have been approved in Europe for thromboprophylaxis in patients with severe CKD (eGFR 15–29 mL/min) not on dialysis, using reduced-dose regimens [25]. Based on pharmacokinetic studies, the US Food and Drug Administration (FDA) also approved the use of reduced-dose dabigatran (75 mg bid) in patients with AF with an eGFR of 15–29 mL/min as well as the use of apixaban (5 mg bid) in patients with AF and end-stage renal disease (ESRD) on dialysis [26,27].…”
Section: Patients With Chronic Kidney Diseasementioning
confidence: 99%